Infection and myelodysplasia: A case report of GATA2 deficiency in a South African patient - Erica‐Mari Nell; Helena Cornellissen; Katherine Hodkinson; Michael F. Urban; Fatima Cassim Bassa; Fatima Bibi Fazel; Tracey Wiggill; Semira Irusen; Zivanai C. Chapanduka (Clinical Case Reports, 2023)
Abstract Rare diseases often result in delays in diagnosis. It is important to recognize conditions that have features of both inborn errors of immunity and predispose to myeloid neoplasia. Here we report a patient with GATA2 deficiency that presented with disseminated non‐tuberculous mycobacterial infection and pancytopenia secondary to myelodysplastic syndrome.